Biphoton Interference in a Double-Slit Experiment - Ananya Paul; Tabish Qureshi (Quanta)
A double-slit experiment with entangled photons is theoretically analyzed. It is shown that, under suitable conditions, two entangled photons of wavelength λ can behave like a biphoton of wavelength λ/2. The interference of these biphotons, passing through a double-slit can be obtained by detecting both photons of the pair at the same position. This is in agreement with the results of an earlier experiment. More interestingly, we show that even if the two entangled photons are separated by a polarizing beam splitter, they can still behave like a biphoton of wavelength λ/2. In this modified setup, the two separated photons passing through two different double-slits, surprisingly show an interference corresponding to a wavelength λ/2, instead of λ which is the wavelength of each photon. We point out two experiments that have been carried out in different contexts, which saw the effect predicted here without realizing this connection.